2004
DOI: 10.1534/genetics.104.034777
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Expressed Sequence Tag (EST) Resource for Wheat (Triticum aestivum L.)

Abstract: This report describes the rationale, approaches, organization, and resource development leading to a large-scale deletion bin map of the hexaploid (2n ϭ 6x ϭ 42) wheat genome (Triticum aestivum L.). Accompanying reports in this issue detail results from chromosome bin-mapping of expressed sequence tags (ESTs) representing genes onto the seven homoeologous chromosome groups and a global analysis of the entire mapped wheat EST data set. Among the resources developed were the first extensive public wheat EST coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Wortman et al (2003) and the International Rice Genome Sequencing Project (2005) recently estimated the number of genes in Arabidopsis and rice to be 28,952 and 37,544, respectively. In light of these gene number estimates and the fact that gene number inflation may be a common artifact within EST assemblies (Close et al 2004;Lazo et al 2004), one might expect that the 33,665 exemplar sequences from Gossypium identified here may be an overestimate of the number of putative genes in the assembly. By their very nature, ESTs undersample the genic content of genomes; at the end of the year 2000, for example, 105,000 Arabidopsis ESTs identified only ∼60% of the genes (The Arabidopsis Genome Initiative 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Wortman et al (2003) and the International Rice Genome Sequencing Project (2005) recently estimated the number of genes in Arabidopsis and rice to be 28,952 and 37,544, respectively. In light of these gene number estimates and the fact that gene number inflation may be a common artifact within EST assemblies (Close et al 2004;Lazo et al 2004), one might expect that the 33,665 exemplar sequences from Gossypium identified here may be an overestimate of the number of putative genes in the assembly. By their very nature, ESTs undersample the genic content of genomes; at the end of the year 2000, for example, 105,000 Arabidopsis ESTs identified only ∼60% of the genes (The Arabidopsis Genome Initiative 2000).…”
Section: Discussionmentioning
confidence: 92%
“…The use of nullisomic-tetrasomic, ditelo- Gill et al , 1996aDelany et al 1995; laboratories. Information on the cDNA libraries is available in Zhang et al (2004) and the development of EST singletons Faris et al 2000;Qi and Gill 2001;Sandhu et al 2001; has been described by Lazo et al (2004). ESTs were mapped to Weng and Lazar 2002;Akhunov et al 2003a;Qi et al chromosome bin locations on the chromosomes via Southern 2004).…”
mentioning
confidence: 99%
“…Chromosome bin mapping and data verification ditelosomic, and deletion lines. The chromosome karyoprocedures have been described by Lazo et al (2004). Loci types detailing breakpoints and chromosome bins for mapped to group 2 chromosomes by any of the 10 mapping the cytogenetic stocks used in the wheat EST mapping labs were confirmed by the University of Minnesota lab on the basis of the autoradiogram image available in the online project can be found online at http://wheat.pw.usda.…”
mentioning
confidence: 99%
“…The procedures used to generate EST data and the bioinformatics pipeline developed for large-scale EST data processing were reported in Lazo et al (2004). EST assembly was carried out using the program Phrap (University of Washington, Seattle, http://www.genome.washington.edu/ UWGC/analysistools/Phrap.cfm).…”
Section: Large-scale Est Generation Data Processing Annotation Andmentioning
confidence: 99%